Аналіз зв'язків між показниками у регіональних соціально-економічних системах - Тутова, О.В. (Економіко-математичне моделювання соціально-економічних систем, 2016)
Connection between gross regional product and social and demographic factors was analyzed in the article. Regional social and economic systems were investigated by the example of the Ukrainian regions with the highest level of human development.